Otimização da produção de celulases de Melanoporia sp. por fermentação submersa - Oliveira, Simone Lopes do Rêgo de (2014)
Cellulases are enzyme complex composed of endoglucanases, exoglucanases and β-glucosidases with several biotechnological applications. However, their production cost is a major obstacle for its industrial application. About 40% of the total cellulase production cost is related to the culture medium used for the microorganism growth. In this context, efficient processes for cellulolytic enzyme production are of technical and economical interest. Thus, the present study aimed to optimize the production of cellulases by Melanoporia sp. using coconut shell powder as substrate in submerged fermentation. The influence of pH and temperature on the enzyme activity was evaluated by univariate experimental design. Then, the composition of the culture medium was sequentially optimized through Plaket -Burman followed by Central Composite experimental designs. The fermentation under optimized conditions was subsequently conducted in bioreactor to evaluate the influen ce of pH control and aeration on enzyme production. The stability of the enzyme was evaluated for 6 and 8 months at 4 °C and - 20 °C, respectively. The ability of the enzyme to hydrolyze coconut shell powder was evaluated at 65 °C and 80 °C using the crude enzyme extract produced by Melanoporia sp. The enzyme activity was determined by the quantification of reducing sugars using DNS method at pH 5.5 and 80 °C (optimum conditions). The composition of the culture medium which provided the highest enzyme yield was: 5 g/L of coconut shell; 15 g/L lactose; 3% tween 80; 1 g/L of KH2PO4 and 0.05 g/L FeSO4; pH 6.5 at 30°C for 72 hours. For batch enzyme production, the cult ure medium using non-delignified substrate, with pH controlled at 6.5, without aeration resulted in an increase of 90% in enzyme activity compared to the fermentation in a rotatory shaker. Under these conditions, the maximal enzyme production was obtained after 24 hours of fermentation. The crude enzyme extract produced by Melanoporia sp. was able to hydrolyze cellulose (coconut shell powder) efficiently, presenting industrial potential for the degradation of lignocellulosic residues. Unlike most of the cellulases produced by Trichoderma species, the strain reported as one of the best producers, the microorganism was capable of producing cellulases efficiently without the need of substrate pretreatment. Another feature of this enzyme complex is its high stability in the crude broth at-20°C e 4 °C